Effect of 5‐hydroxytryptamine receptor 4 agonist mosapride on human gastric accommodation. Issue 9 (September 2015) - Amano, T.; Ariga, H.; Kurematsu, A.; Yamato, S.; Morioka, S.; Masaka, A.; Kanazawa, M.; Fukudo, S.
Abstract Background Impaired gastric accommodation is one of the major features of functional dyspepsia. Mosapride citrate is a 5‐hydroxytryptamine receptor 4 (5‐HT4) agonist, which is shown to improve upper abdominal symptoms. However, effect of mosapride on gastric accommodation was not clear. We tested the hypothesis that mosapride enhances the gastric accommodation in normal individuals. Methods Fourteen male healthy volunteers completed this study. Single administration of mosapride or placebo was performed randomly with more than 1‐week interval. Subjects swallowed a triple‐lumen polyvinyl tube with a polyethylene bag. The bag was positioned in the proximal stomach and the minimal distending pressure (MDP) was determined. The ramp distension starting from the MDP was then performed and subjects were instructed to score their perception using ordinate scales. Next the intra‐bag pressure was set at MDP + 2 mmHg and a liquid meal was administered 30 min later, and the intra‐bag volume was recorded for 60 min. We compared the MDP, perception scores, and the intra‐bag volume changes by administering placebo and mosapride. Key Results Minimal distending pressure was not significantly different in subjects receiving mosapride or placebo. Treatment with mosapride had no effect on intra‐bag pressures or volumes inducing first sensation or discomfort. Gastric accommodation, expressed as the difference between pre‐ and postmeal intra‐bag volumes, and the percent change of the intra‐bag volumes by the meal was significantly enhanced by mosapride compared with placebo. Conclusions & Inferences This is the first study clearly demonstrating that single administration of 5‐HT4 agonist can enhance gastric accommodation in humans. (Umin.ac.jp, number UMIN000014063)